Penghangat Cairan Infus Dengan Sistem Monitoring Berbasis IoT - Laia, Frengki Ditus; Panjaitan, Christin Erniati (MEANS (Media Informasi Analisa dan Sistem), 2025)
This study develops an Internet of Things (IoT) based infusion fluid warmer with a remote monitoring system to prevent hypothermia in patients. This tool uses several main components in controlling the temperature of the infusion fluid through the blynk application or manually, the components are NodeMCU ESP8266, temperature and humidity sensors (DHT11 sensors), 5V DC relays, 220Volt AC digital thermostats, and incandescent lamps. The infusion fluid is warmed to a minimum temperature of 39°C to a maximum temperature of 40°C before being transfused to the patient, with a system that automatically maintains the temperature within that range through a warming cycle from the incandescent lamp. With the NodeMCU ESP8266 component and the blynk IoT application, this tool can be monitored and controlled remotely. This tool can also be accessed and controlled manually via a 220Volt AC digital thermostat and several components such as switches on the infusion fluid warmer. Testing shows that this tool works effectively, with accurate and responsive monitoring results in maintaining the temperature of the infusion fluid. In addition, the automatic system ensures that the fluid temperature remains optimal without the risk of overheating. With this IoT-based infusion warmer system, it can make it easier for the medical team to control and monitor the infusion fluid that is being warmed both from close range and from a distance. This tool provides an innovative solution in the care of hypothermia patients, especially in emergency situations or in hospital emergency rooms that have the potential to increase the efficiency of health services in a hospital.